2017
DOI: 10.1007/s13197-017-2690-9
|View full text |Cite
|
Sign up to set email alerts
|

Swelling and infusion of tea in tea bags

Abstract: The present study deals with swelling and infusion kinetics of tea granules in tea bags. The swelling and infusion kinetics of tea bags differing in tea loading and tea bag shapes were compared with loose tea. Increment in temperature and dipping frequency of tea bag in hot water increased the infusion kinetics of tea bags. Reduction in particle size enhanced the swelling and infusion kinetics of tea in a tea bag. The effects of tea particle size, tea bag dipping rate, loading of tea granules in tea bag and te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 14 publications
1
7
0
1
Order By: Relevance
“…PS reduction improved the swelling capacity and IK of tea in a tea bag [29], [32]. This result was in agreement with observation made by Raosaheb [33] that particle fractions with smaller PS (500-250 μm) showed faster infusion.…”
Section: B Role Of Ps In Tea Infusionsupporting
confidence: 90%
See 2 more Smart Citations
“…PS reduction improved the swelling capacity and IK of tea in a tea bag [29], [32]. This result was in agreement with observation made by Raosaheb [33] that particle fractions with smaller PS (500-250 μm) showed faster infusion.…”
Section: B Role Of Ps In Tea Infusionsupporting
confidence: 90%
“…The key factors influencing the IK of tea bags are tea bed brought into being inside the tea bag, tea bag shapes and size, stirring outside the tea bag, PS of tea granules, tea bag loading, brewing temperature and dipping frequency [29]. Some findings observed that a rise in temperature and dipping frequency (rate) of tea bag in hot water resulted in an increase in the IK of tea bags [29]. Hence the infusion profile of tea is being enhanced with increment in brewing temperatures and reduction in PS [3].…”
Section: A Effect Of Dipping Temperature Infusion Time and Dipping Fr...mentioning
confidence: 99%
See 1 more Smart Citation
“…The particle size of the herbs used in the Tea was large (1.80-1.20 cm) with 51 by 50mm bag size in which continuous shaking was carried out whereas in the other set small particles of (250-500 mm) with (40mm) bag size and no change (static) were observed. The extraction rate was profound in the tea-bag which are continuously sunk and dipped inside compared to the floating tea-bags [54] .…”
Section: Alloxan and Streptozotocin Inducedmentioning
confidence: 94%
“…The formulated tea bags were immersed in 240 mL distilled water and brewed at 80°C for 5 min. The maximum infusion time for the tea bag was <30 s to 10 min [ 19 ]. This infusion extract was used to formulate the ointment of different strengths for wound healing activity.…”
Section: Methodsmentioning
confidence: 99%